(untitled) (Materiali di Estetica. Terza serie, 2020)
Maria Zambrano is one of the thinkers who, together with Simone Weil and Hannah Arendt, gave a fundamental contribution in order to the understand the historical-political events that marked the European history of the 20th century. Zambrano’s thought appears to many scholars to be divided between a reflection on history and democracy and a "knowledge of the soul" oriented towards existential themes. The Spanish philosopher not only reflected on the idea of ​​Europe, but personally experienced the most dramatic events of Europe during the 20th century. From the historical-political tragedy of the Europe of her time Zambrano derives the intuition of a redemption, which is not an individual salvation, but is the possibility of hope, of a new idea of ​​Europe, fruit of its deepest crisis. Zambrano’s thought on Europe highlights the need, today stronger than ever, for an experience of history lived in the tension between its dramatic, violent, destructive aspects and the opening to dreams, delusions of grandeur and the need for truth. Zambrano is a philosopher of hope who teaches the importance of a tragic vision of history.